2017
DOI: 10.1371/journal.pone.0176061
|View full text |Cite
|
Sign up to set email alerts
|

A screen for protective drugs against delayed hypoxic injury

Abstract: Despite longstanding efforts to develop cytoprotective drugs against ischemia/reperfusion (IR) injuries, there remains no effective therapeutics to treat hypoxic injury. The failure of traditional strategies at solving this problem suggests the need for novel and unbiased approaches that can lead to previously unsuspected targets and lead compounds. Towards this end, we report here a unique small molecule screen in the nematode C. elegans for compounds that improve recovery when applied after the hypoxic insul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
4
1

Year Published

2018
2018
2021
2021

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 43 publications
0
4
1
Order By: Relevance
“…The ability of doxycycline to induce acute cardioprotection was also tested, by delivering the drug to ex-vivo perfused hearts prior to ischemia and during reperfusion. However, in contrast to previous reports (29), no significant protective effect was observed (functional recovery: doxycycline 40±19% vs. vehicle 34±9%, p=0.78; infarct: doxycycline 66±6% vs. vehicle 49±5%, p=0.11) ( Fig. 3E/F).…”
Section: Atf5-dependent Cardioprotection By Doxycyclinecontrasting
confidence: 95%
See 1 more Smart Citation
“…The ability of doxycycline to induce acute cardioprotection was also tested, by delivering the drug to ex-vivo perfused hearts prior to ischemia and during reperfusion. However, in contrast to previous reports (29), no significant protective effect was observed (functional recovery: doxycycline 40±19% vs. vehicle 34±9%, p=0.78; infarct: doxycycline 66±6% vs. vehicle 49±5%, p=0.11) ( Fig. 3E/F).…”
Section: Atf5-dependent Cardioprotection By Doxycyclinecontrasting
confidence: 95%
“…Although herein we chose a 6 h delay between drug administration and IR injury, to permit induction of the UPR mt gene program, a recent report claimed acute cardioprotection by tetracycline antibiotics delivered 30 min prior to ischemia (29). Our inability to reproduce this phenomenon may have been due to an observed low solubility of doxycycline in Krebs-Henseleit perfusion buffer, such that the microfiltration necessary for successful mouse cardiac perfusion (37) may have limited doxycycline bioavailability in our experiments.…”
Section: Discussionmentioning
confidence: 99%
“…We first tested all compounds against the model nematode C. elegans and the plant parasitic nematode H. schachtii in direct exposure assays. The nematode C. elegans is frequently used in studies involved in investigating compounds’ bioactivities against multicellular organisms ( Sun et al, 2017 ; Al Banna et al, 2018 ; Liao, 2018 ). The nematode H. schachtii is one of the devastating pathogens of several economically valuable crops ( Steele, 1965 ; Muller, 1999 ).…”
Section: Discussionmentioning
confidence: 99%
“…The screening window, commonly assessed using the Z-factor, ensures detection of true-positive hits and limits the number of false-negative and false-positive hits. Additionally, most published studies have been limited to single-readout phenotypes, such as cell survival ( Sharma et al, 2017 ; Sun et al, 2017 ), expression of a single marker ( Ghazizadeh and Majd, 2020 ), or reporter screens ( McLendon et al, 2017 ). While these studies revealed great insight into cardiomyocyte biology, they have not described a general and unbiased screening strategy that can be applied to other cell types and used at scale.…”
Section: Introductionmentioning
confidence: 99%